2008
DOI: 10.1021/jp076603f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and High Hydrogen Storage Capacity of Zeolite-Like Carbons Nanocast Using As-Synthesized Zeolite Templates

Abstract: As-synthesized zeolite β has been successfully used as a template for the preparation, via chemical vapor deposition, of well ordered zeolite-like carbon materials. The carbon materials have high surface area (1720−2535 m2/g) and high pore volume (1.09−1.56 cm3 g-1) and exhibit some zeolite-like structural ordering replicated from the zeolite template. Carbon materials prepared at 800 and 850 °C are nongraphitic and retain the particle morphology of the zeolite templates. Carbon prepared at 900 °C contains som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 34 publications
10
67
0
1
Order By: Relevance
“…34,48,51 Similar hysteresis loops in isotherms have also previously been observed for ordered porous carbons using other kinds of zeolites as the hard template. 29,30,33,36,47 On the other hand, the representative TEM images of the 10Xc-70 in Figures 3b and S2 (Supporting Information) further demonstrate that a part of the carbon precursors does have deposits on the external surface of the 10X zeolite template, and the carbons do have some randomly distributed mesopores, which are in excellent agreement with XRD and N 2 isotherms observations.From the pore structure parameters listed in Table 1, we can obviously find that the pore textures of carbons are largely dependent on the preparation conditions, namely, surface area and total pore volume of carbons derived from the liquid−gas two-step routes are much larger than ones from the single gas CVD process. As expected, carbons that exhibit well-developed zeolite-like orderings generally have a higher proportion of micropore surface area and pore volume.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…34,48,51 Similar hysteresis loops in isotherms have also previously been observed for ordered porous carbons using other kinds of zeolites as the hard template. 29,30,33,36,47 On the other hand, the representative TEM images of the 10Xc-70 in Figures 3b and S2 (Supporting Information) further demonstrate that a part of the carbon precursors does have deposits on the external surface of the 10X zeolite template, and the carbons do have some randomly distributed mesopores, which are in excellent agreement with XRD and N 2 isotherms observations.From the pore structure parameters listed in Table 1, we can obviously find that the pore textures of carbons are largely dependent on the preparation conditions, namely, surface area and total pore volume of carbons derived from the liquid−gas two-step routes are much larger than ones from the single gas CVD process. As expected, carbons that exhibit well-developed zeolite-like orderings generally have a higher proportion of micropore surface area and pore volume.…”
supporting
confidence: 79%
“…reported by the group of Mokaya, 29,34,36,40,47,51,54 who demonstrated that a significant proportion of micropores at 0.6 nm is beneficial for enhancing the hydrogen storage capacities, especially for high pressures. Therefore, we have reason to believe that the carbons reported here probably also have high hydrogen storage uptakes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon samples cast from zeolite b exhibited a particularly high hydrogen uptake of 6.9 wt % at 20 bar and 2.6 wt % at 1 bar at À196 8C. [238,239] However, for all nanoporous carbons tested, the room temperature absorption was much lower. Although the isosteric heat of adsorption in the smaller micropores (8 kJ mol…”
Section: Hydrogen Storagementioning
confidence: 97%
“…Unlike the soft templating method, in which the surfactant arranges itself during the synthesis process in order to give rise to the desired structure if the appropriate synthesis conditions are met, the hard templating method relies on the use of preshaped solid forms as templates, which, upon deposition of the desired oxide species and removal of the "mold" gives rise to the final desired material. This method may be found in the literature with other names such as nanocasting [205,225,226], exotemplating [227], or repeated templating method [207]. Porous Al 2 O 3 supports prepared by anodic oxidation (AAO or anodized aluminium oxide) [228,229] were used initially as a mold to prepare carbons, metals, or other nanostructures by a variety of techniques such as electrodeposition [230], Chemical Vapour Deposition (CVD) [231][232][233], Plasma-Enhanced Chemical Vapour Deposition (PE-CVD) [234], or Atomic Layer Deposition [235].…”
Section: Synthesis and Structurementioning
confidence: 99%